Biofidelity assessment of the activen human body model compared to volunteer braking and steering maneuvers - Xiao, Yang (My University, 2017)
Active human body models have contributed to the safety device design and helped build a safer road. Validation is essential for the development of all human models and SAFER A-HBM is no exception. The validation of SAFER A-HBM in multidirection would contribute to the further development of it. Recent research on human body behaviors has been focusing on the frontal and lateral loading direction. But few research looks into the oblique direction. The recently developed SAFER AHBM is able to work in the ominidirection and needs to validate its effectiveness with the experiment data. By repeating in-vehicle volunteer tests in simulations, which involves oblique maneuvers, visual inspection and correlation analysis have been made between SAFER A-HBM and volunteers. Different setups, such as passive SAFER A-HBM, a different seat and without foot support, are also investigated. Implementing of omni-directional muscles in SAFER A-HBM improves the prediction of head kinematics in pre-crash phase, compared to the model without active muscle. However, the muscle response in lateral direction is still needed to be tuned compared to volunteer response.
Keywords: Livsvetenskaper; Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Teknisk mekanik; Life Science; Transport; Sustainable Development; Innovation & Entrepreneurship; Applied Mechanics